Effects of periodontal disease on the proteomic profile of the periodontal ligament - Lopes, Maria Eduarda Scordamaia [UNESP] (2025)
Periodontal disease affects over 1 billion people globally. This study investigated how periodontitis affects the protein profile of the periodontal ligament (PDL) in rats. Eight Holtzman rats were divided into control and experimental periodontitis groups. The PDL was isolated using laser capture microdissection and protein extracts were analyzed by mass spectrometry. Data analysis utilized specialized software, and Gene Ontology enrichment analysis identified significant protein functions. The data are available via ProteomeXchange with identifier PXD055817. Proteins such as SerpinB1, C5, and Lgals3 were validated through immunohistochemistry, and their gene expression was examined in an in vitro human PDL cell line. This study identified 1326 proteins, with 156 unique to the control group, 294 unique to the periodontitis group, and 876 common to both groups. Enrichment analysis revealed that proteins associated with the regulation of enzyme activity and RNA binding were significantly represented in the periodontitis group. There were increased levels of SerpinB1, C5, and Lgals3 in the periodontitis group based on proteomic and immunohistochemical analyses. Furthermore, these targets showed increased gene expression in stimulated human PDL cells. This study provides insights into the periodontitis-related alterations in the protein composition of the PDL and PDL cells, identifying both novel and previously known disease-associated proteins. Significance: The periodontal ligament plays a crucial role in oral functions by providing structural support to the tooth. Due to the presence of undifferentiated mesenchymal cells, research into its regenerative capacity is ongoing. Pathological conditions can affect these functions and protein composition. Currently, there is a lack of comprehensive research specifically focusing on evaluating the periodontal ligament in both healthy and diseased states. This pioneering study screened for protein alterations and the mechanisms related to periodontitis. The possibility of using proteomic analysis to evaluate the protein alterations that occur in periodontitis, a disease with a high global incidence, could provide therapeutic targets and new biomarkers for future clinical studies.